Effect of Die Geometry on Thermal Fatigue Analysis of Aluminium Alloy (A02240) Using Pressure Die Casting Process - Dewangan, Poshan; Dewangan, Ved Prakash; Maurya, Sushil Kumar; Singh, Lokesh (International Journal of Scientific Research in Civil Engineering, 2021)
Dies for aluminium alloys die-casting fail because of a great number of different and simultaneously operating factors. Some of them may be controlled to some extent by the die-casting experts. In the process of the die-casting the primary source of loading is cyclic variation of the temperature; the influence of other loads is relatively insignificant. For economical production of aluminium and aluminium alloys die castings it is important that the dies have a long working life. The replacement of a die is expensive in both: money and production time. The die design, the material selection and the process thermal fatigue stress which is the consequence of the working conditions, the inhomogeneous and to low initial temperature of the die, contribute to the cracks formation. The main objective of this work to find out The thermal fatigue of die casting saffil-reinforced aluminium alloy (96%Al2O3/4%SiO2) causes reduction in tool life and seriously affects the surface conditions such as microstructure, hardness, surface finish and residual stresses. The size and location of cooling channels relative to the surface of the die, which affect the thermal stresses and fatigue life of dies. This work focus on thermal fatigue analysis of Aluminium alloy pressure die casting process and analyses the effect of coolant channel location on temperature distribution and fatigue parameters such as life, damage, equivalent alternating stress and biaxiality using ANSYS Workbench 17.1 finite-element package.
Keywords: Aluminium Alloys; Die-casting; Thermal Fatigue; Temperature Distribution; Life